KARAKTER RESPIRASI DAN MINERALISASI KARBON ORGANIK PADA SAMPEL TANAH DIKOLEKSI DARI PULAU BANGKA - Maman Rahmansyah; Suliasih Suliasih (BERITA BIOLOGI, 2016)
The study was designed to explore soil biomass content and soil enzymatic activities that involved in carbon organic soil mineralization. Samples of soil were collected from two locations in Bangka Island. Bulk samples of top soil (TP) and excavated (TG)  were collected from garden soil in Pangkalpinang. Other soils were gathered from forest floor (TU), beneath pelawan (Tristaniopsis merguensis Griff.) trees which is endemic plant to North Bangka forest. Soil biological character was evaluated by measuring soil microbial population, respiration rate, and cellulase and amylase activities. Experiments were carried out in Research Center for Biology, Indonesian Institute of Sciences, on dried soil treatment (Control), soil moistened with 5 mL H2O in 100g soil (Gluc.0), and soil moistened with 5 mL 1% glucose solution (Gluc.1). Bacterial population obtained was higher than fungal population in all soil samples. Soil respiration activity in TU after treatment was 4.51±0.49; 5.26±0,79; and 8.28±1.41 ppm CO2/100g-soil/5-minutes, respectively. Meanwhile , respiration in TP  were 3.65 ± 2.12; 3.57 ± 1.18; and 7.94 ± 1.05 ppm CO2/100g-soil/5-minutes; and in the TG are 2.61 ± 0.70; 3.34 ± 0.94; and 5.46 ± 2.30 ppm CO2/100gsoil/5-minutes. Cellulase activity of all samples were not significantly different. Forest soil cellulase activity was significantly different compared to garden soil. Glucose induction was positively increased amylase activity compared to cellulase. Soil enzyme, soil respiration activities and microbial population of forest soil could be used as a reference to recover degraded land in Bangka Island.